TEACHERS’ PERCEPTIONS ON THE IMPLEMENTATION OF FLIPPED CLASSROOM MODEL IN LEARNING WRITING - Anggrita Nurfaiziyah; Zainul Aminin (IKIP Siliwangi, 2021)
The flipped classroom is a relatively recent method of the teaching-learning process. Based on the current pandemic of COVID-19, a flipped classroom is one of the suitable learning models to use. It aims to improve student engagement and performance by bringing technology to the teaching-learning process outside of the classroom. However, the flipped classroom model is not widely used in Indonesia. This study discusses instructors' perspectives on using the flipped classroom concept in teaching writing. The subjects of this study were six Senior High School English teachers that used the flipped classroom to teach writing for the twelfth grade of Senior High School. The data were collected by using an open questionnaire and unstructured interview. The researchers provide the data by using a descriptive qualitative approach. This research shows that the flipped classroom is one of the modern learning models with several benefits and facilitates the teacher and the students in the teaching-learning process. The teachers can use the material they have prepared (in videos, PowerPoint, or modules) to teach several classes while the students have an opportunity to be more independent and active in learning because of their high curiosity. Keywords: Flipped Classroom, Writing, Teachers’ Perceptions